Sphingosine signaling dysfunction in airway cells as a potential contributor to progression from protracted bacterial bronchitis to bronchiectasis in children. Issue 6 (16th March 2020) - Hodge, Sandra; Macowan, Matthew; Liu, Hong; Hamon, Rhys; Chen, Alice C.‐H.; Marchant, Julie M.; Pizzutto, Susan J.; Upham, John W.; Chang, Anne B.
Abstract: Aim: Protracted bacterial bronchitis (PBB) is considered a potential precursor to bronchiectasis (BE) in some children. We previously showed that alveolar macrophages (AM) from children with PBB or BE have a similar significant defect in phagocytic capacity, with proinflammatory associations. We hypothesized that the mechanisms responsible for this defect involve dysregulation of the sphingosine‐1‐phosphate (S1P) signaling pathway, as we have found in adult inflammatory lung diseases. Method: We employed a Custom TaqMan OpenArray to investigate gene expression of S1P‐generating enzymes: sphingosine kinases (SPHK) 1/2, S1P phosphatase 2 ( SGPP2), S1P lyase 1 ( SGPL1 ), S1P receptors ( S1PR ) 1/2/4/5; proinflammatory cytokines TNF‐α ( TNF ) and IFNγ ( IFNG ), the cytotoxic mediator granzyme B ( GZMB ), and inflammasomes AIM2 and NLRP3, in bronchoalveolar lavage from 15 children with BE, 15 with PBB and 17 age‐matched controls, and determined association with clinical/demographic variables and airway inflammation. Result: Significantly increased expression of S1PR1, S1PR2, and SPHK1 was noted in PBB and BE AM vs controls with increased SGPP2 only in PBB. TNF, IFNG, AIM2, and NLRP3 were significantly increased in both disease groups with increased GZMB only in PBB. There were no significant differences in the expression of any other S1P‐related mediator between groups. There were significant positive associations between Haemophilus influenzae growth and expression of S1PR1 and NLRP3 ; between S1PR1 and S1PR2, NLRP3 and IFNG ; between S1PR2 and AIM2, SPHK1, and SPHK2 ; and between SPHK1 and GZMB, IFNG, AIM2, and NLRP3 . Conclusion: Children with PBB and BE share similar S1P‐associated gene expression profiles. AM phagocytic dysfunction and inflammation in these children may occur due to dysregulated S1P signaling.